2021
DOI: 10.1038/s41598-021-95710-3
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 receptor blockers are anti-inflammatory drugs inhibiting both circulating monocytes and macrophages including THP-1 cells

Abstract: P2Y12 blockade improves patient outcomes after myocardial infarction. As well as antithrombotic effects, anti-inflammatory effects may contribute to this beneficial clinical outcome. Here we aimed to identify potential anti-inflammatory effects of P2Y12 receptor blockers on monocytes and macrophages. Using flow cytometry, migration assays, flow chambers and RNA microarrays, we investigated the effects of adenosine diphosphate (ADP) and P2Y12 receptor blockers on blood monocytes, THP-1 monocytes and THP-1 monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…One possible chemoattractant is adenosine diphosphate (ADP), released from dense granules by activated platelets, and was shown to attract monocytes and macrophages through the action of the P2Y 12 receptor in recent studies. [50][51][52] Although our results indicated that CCL5 was mainly responsible for the chemotactic effect of platelet supernatants, an involvement of ADP appears feasible since remnant levels of cangrelor in the platelet supernatants might be sufficient to reduce chemotaxis. In addition, cangrelor inhibited the release of serotonin, which is likewise stored in dense granules, and this could explain why a strong inhibition of monocyte chemotaxis toward supernatants of cangrelor þ ASA-treated platelets was observed, while CCL5 secretion was poorly affected by this combined treatment.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…One possible chemoattractant is adenosine diphosphate (ADP), released from dense granules by activated platelets, and was shown to attract monocytes and macrophages through the action of the P2Y 12 receptor in recent studies. [50][51][52] Although our results indicated that CCL5 was mainly responsible for the chemotactic effect of platelet supernatants, an involvement of ADP appears feasible since remnant levels of cangrelor in the platelet supernatants might be sufficient to reduce chemotaxis. In addition, cangrelor inhibited the release of serotonin, which is likewise stored in dense granules, and this could explain why a strong inhibition of monocyte chemotaxis toward supernatants of cangrelor þ ASA-treated platelets was observed, while CCL5 secretion was poorly affected by this combined treatment.…”
Section: Discussionmentioning
confidence: 56%
“…A possible explanation for this observation might be that the combination of ASA and cangrelor can inhibit the release of several chemoattractants from platelets, other than CCL5. One possible chemoattractant is ADP, released from dense granules by activated platelets, and was shown to attract monocytes and macrophages through the action of the P2Y 12 receptor in recent studies [50][51][52]. Although our results indicated that CCL5 was mainly responsible for the chemotactic effect of platelet supernatants, an involvement of ADP appears feasible since remnant levels of cangrelor in the platelet supernatants might be sufficient to reduce chemotaxis.…”
Section: Accepted Manuscriptmentioning
confidence: 53%
See 1 more Smart Citation
“…The P2Y 12 receptor is mainly expressed on platelets, but also on vascular smooth muscle cells and immune cells including mast cells, monocytes, macrophages, and lymphocytes [ 31 ]. Inhibiting these immune cells via P2Y 12 inhibitors may exert anti-inflammatory effects beyond the well-known anti-platelet effects of these inhibitors [ 32 ]. Myocardial necrosis was reduced and ejection fraction was preserved in ischemia reperfusion injury in P2Y 12 knockout mice in a previous study by our group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may also relate to ticagrelor’s preferential effects in increasing extracellular adenosine concentrations. These have been recognized as potential benefits of P2Y 12 receptor antagonists ( 10 ).…”
Section: The Platelet P2y 12 Receptor and Its Role...mentioning
confidence: 99%